Experimental Studies on Endothermic Reversible Reaction of Salts for Cooling. Issue 13 (6th August 2021) - Desai, Fenil; Atayo, Asonganyi; Prasad, Jenne Sunku; Muthukumar, Palanisamy; Rahman, Muhammad; Asmatulu, Eylem
Abstract: Thermal energy storage has a potential future to store renewable energy. Thermochemical energy storage (TCES) is the most promising and possesses more advantages over sensible and latent heat thermal storage systems such as higher energy storage density and ambient temperature storage. The major concern at this time for TCES is to find the material or combination of materials which can be thermally stable, have high energy storage density and be nontoxic. In this paper, Fertilizer based salts as a potential TCES material for cooling applications are studied experimentally. To produce a cooling effect, salts are dissolved in water and a drop in temperature is measured experimentally. Systematic evaluation for the combination of Nitrogen (N), phosphorus (P) and potassium (K) based salts are used to produce the cooling effect. Individuals and 14 various mixtures of NPK salts such as NH4 Cl, K2 SO4, (NH4 )2 CO, NH4 NO3, KNO3, NaNO3, and NH4 H2 PO4 have been studied experimentally. The cooling effect in the range of 200-400 kJ per kg of salt is produced when the salt is dissolved in the water. It is observed that an average of 24 °C to 28 °C instant decrease in temperature is noticed when 60-80 g of water is added to the mixture of salt. Among the investigated salt mixture, NPK4 yielded a maximum temperature drop of 30 °C.